Usaha Meminimalkan Risiko Pembiayaan Pada Pegadaian Syariah - Romadzuhri Nurbanatra; Muhammad Nafik H.R (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
This research adopts a qualitative approach with a study case methodology. Data collection is done through personal interviews with informants, who are the head of branch, marketing staffs, administration staffs and clients of Pegadaian branch Blauran, Surabaya. Secondary data is also collected from documents pertinent to risk mitigation in Islamic Pawnshop (Pegadaian). The technique of analysis employed in this research is the Pattern-Matching technique accompanied with the narration of results of the interviews Results from this research suggest that the mitigation of funding risks have not been optimized in Islamic Pawnshop (Pegadaian). The risk mitigation process has only been formalities done withoutevaluation in order to comply with the standard procedures. Thus said, funding risks in Islamic pawnshop have not yet been optimally mitigated.